Will migrant workers rescue rural regions? Challenges of creating stability through mobility - Aure, Marit; Førde, Anniken; Magnussen, Tone (Journal of Rural Studies, 2018)
Accepted manuscript version. Published version available at https://doi.org/10.1016/j.jrurstud.2018.03.005 . Accepted manuscript version, licensed CC BY-NC-ND 4.0. Many rural communities experience new growth through in-migration. In Herøy, Northern Norway, this is a result of increased labour migration in the fishing industry and a comprehensive effort by the municipality to encourage migrant workers to settle there. This paper addresses the ambiguities of creating stability through mobility. Through a case study from Herøy, we explore the complex relations between migrants' mobile economic practices and social integration processes by analysing how migrants engage with Herøy's landscape in multiple manners. This landscape entails networks of people and relations, materialities, dreams and hopes. Studying engagement, in addition to contestations and intersecting trajectories, we analyse how the landscape of those on the move is interrelated with that of those “being moved through”. We argue that creating stability in rural communities by encouraging migrant settlement requires going beyond economic integration – emphasising the more versatile and vulnerable processes of relating to unfamiliar places and worlds. It also requires an understanding of stability that embraces uncertainty and opens up towards various forms of belonging.